2014
DOI: 10.1063/1.4868691
|View full text |Cite
|
Sign up to set email alerts
|

Spin transistor operation driven by the Rashba spin-orbit coupling in the gated nanowire

Abstract: The theoretical description has been proposed for the operation of the spin transistor in the gate-controlled InAs nanowire. The calculated current-voltage characteristics show that the current flowing from the source (spin injector) to the drain (spin detector) oscillates as a function of the gate voltage, which results from the precession of the electron spin caused by the Rashba spin-orbit interaction in the vicinity of the gate. We have studied two operation modes of the spin transistor: (A) the ideal oper… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 27 publications
0
24
0
Order By: Relevance
“…and we shall assume that a Rashba interaction region, centered around the position x R and extending over a width W R , exists along such direction and can be described by the profile model (24). The total photoexcited electron density (44) consists of the two terms Eqs. (31) and (32) that, in the case of the Gaussian pulse (45), reduce to…”
Section: Gaussian Electric Pulse In the Presence Of A Rashba Barriermentioning
confidence: 99%
See 1 more Smart Citation
“…and we shall assume that a Rashba interaction region, centered around the position x R and extending over a width W R , exists along such direction and can be described by the profile model (24). The total photoexcited electron density (44) consists of the two terms Eqs. (31) and (32) that, in the case of the Gaussian pulse (45), reduce to…”
Section: Gaussian Electric Pulse In the Presence Of A Rashba Barriermentioning
confidence: 99%
“…This clearly appears when comparing the locations of the two counterpropagating partner wavepackets at t = 1 ps (dash-dotted green curves): while in the absence of Rashba interaction they would be located at symmetric positions x = ±0.5µm, the rightmoving one has been boosted by the Rahsba region further off from the origin, as compared to the left-moving one. (44)] is shown at various snapshots: t = 0.05 ps (thin solid curve), t = 0.5 ps (solid curve), t = 0.66 ps (dashed curve) and t = 1.0 ps (dash-dotted curve). Due to the increase of velocity (13) ascribed to the Rashba interaction, the right-moving wavepacket is "boosted" by the Rashba barrier, as compared to its left-moving photoexcited partner that does not impact the barrier.…”
Section: A Photoexcitation Far From the Rashba Regionmentioning
confidence: 99%
“…The effect of Rashba spin-orbit coupling, which breaks the conservation of spin axis in edge state [20,[78][79][80][81][82][83][84][85][86][87][88], can introduce additional scattering processes even within right-moving and left-moving channels. The presence of Rashba interaction in 2D TIs could be ascribed to an inversion asymmetry mechanism in the heterostructure or to strain effect [89][90][91][92][93][94], that could be induced, for instance, by an external electric field [95,96]. In this way, the splitting of Cooper pairs can occur within the same channel, without any breaking of time-reversal symmetry.…”
Section: Introductionmentioning
confidence: 99%
“…The full explanation has been given by the further studies, which have shown that the predicted weak spin filter effect 17 can be strengthened by the electron-electron interaction leading to the nearly 100 % spin polarization in the regime of the single-mode transport 13 . QPCs with the SO interaction have been successfully used as the spin injector and detector in the recent experimental realization of the spin transistor 20,21 , in which about 10 5 times greater conductance oscillations have been observed as compared to the conventional spin-field effect transistor based on ferromagnets 22,23 .…”
Section: Introductionmentioning
confidence: 99%